Adolescents’ mental health concerns, reported with an idiographic assessment tool - Thomas Kristian Tollefsen; Sabrina Michelle Darrow; Simon-Peter Neumer; Turid Suzanne Berg-Nielsen (BMC Psychology, 2020)
Abstract Background Adolescents’ self-defined concerns about their mental health are understudied. Yet gaining insight into the individual concerns of this group could be helpful in providing better services to the adolescent population. In this study, an idiographic procedure called Assert was used to increase our knowledge of which concerns are reported by adolescents as the most salient, in a primary mental health care situation. Method 231 unique concerns were reported by 70 adolescents in a primary mental health context in Norway. These concerns were analysed qualitatively by a group of experts, to define categories. The distribution of these categories, and differences in gender and age, were analysed quantitatively. The alleviation experienced on the subjective concerns over the course of counselling was measured. Two linear multilevel models were analysed, to examine whether alleviation on self-defined concerns, as measured with Assert, differed-based on the main category of the concern or the number of times Assert was used. Results Three main categories of concerns emerged, related to (1) Self, (2) Relationships and (3) Life domains; as well as nine sub-categories: (1a) Autonomy, (1b) Mental health, (1c) Somatic health, (2a) Improving of relationships, (2b) Feeling safe from people around them, (2c) Taking responsibility for others, (3a) School, (3b) Work and (3c) Spare time. Girls reported fewer Life domain concerns than boys. Younger adolescents (12–16) more frequently reported no Self concerns, and older adolescents (17–23) more frequently reported no Relationship concerns. The adolescents felt less bothered by their subjective concerns after counselling, and there were some differences in alleviation depending on the category of concern. Conclusions The adolescents defined their own concerns at the start of counselling and were less troubled by these concerns after counselling. The content of the concerns might suggest that these adolescents experienced a need to improve across several arenas: personal, relational and academic. Research to extend the current study, to understand individual adolescent concerns, should include contextual and social factors and personal characteristics—and explore how counselling interventions can best help alleviate these personal concerns.